Family smoking behavior and stunting among children in rural areas of Sleman, Yogyakarta: A case-control study - Panggabean, Eva Rortiana; Deta, Elisabeth; Yuningrum, Hesti; Trisnowati, Heni (Universitas Udayana, 2023)
Background and purpose: Stunting is one of the public health concerns in Indonesia. The prevalence of stunting among children under five in Kalasan Sub-district, Sleman District, Yogyakarta was high at 17.01%. One of the significant predictors of stunting is parental/family smoking behavior. This study aims to portray the smoking behavior of family members and its association with stunting. Methods: We used a quantitative method with a case-control design. The study was conducted in Tamanmartani Village, one area with a high incidence of stunting. The cases were 45 children under five years with stunting based on the public health center’s data and 45 children with normal nutritional status were selected as control. The data was collected by structured interviews using an online questionnaire which included children’s and mother’s characteristics, and smoking behavior among family members. Data was then analyzed descriptively and a Chi-square test was performed to assess the association between variables and stunting. Results: Children who experience stunting are mostly at the age of 24-35 months (35.6%), female (53.3%) and with family income below minimum wages (62.2%). The smoking behavior among the family was slightly higher among cases (66.7%) than controls (64.4%). Most smoking family members in both groups were smoking outside the house. There was no statistically significant association between all variables with stunting, however, we found a potential association between the father’s smoking, type of cigarette, and higher spending on cigarettes with stunting. Conclusion: Smoking among family members was high in both groups, and smoking among fathers is a potential predictor of stunting. Health promotion strategies to reduce smoking habits, smoke-free home innovations, and cessation services should be conducted to reduce and prevent stunting and to improve health.